Phase I study of etoposide, cisplatin and irinotecan triplet in patients with advanced-stage small-cell lung cancer - Briasoulis, E.; Samantas, E.; Kalofonos, H.; Skarlos, D.; Makatsoris, T.; Christodoulou, C.; Fountzilas, G.; Bamias, A.; Dimopoulos, M.A.; Kosmidis, P.; N. Pavlidis (Cancer Chemotherapy and Pharmacology, 2005)
The irinotecan-cisplatin combination has emerged as a new standard for the treatment of advanced-stage small-cell lung cancer (AS-SCLC). To move forward we developed a 3-day regimen of cisplatin, etoposide and irinotecan. Successive cohorts of AS-SCLC patients were treated with irinotecan administered as a single 1-h infusion in combination with fixed doses of cisplatin (20 mg/m 2) and etoposide (75 mg/m2), both given for three consecutive days (ECI regimen). Irinotecan dose was escalated from 60 mg/m 2 by 40-mg/m2 increments. At mid-step between the maximum tolerated dose (MTD) and the previous dose level, patients were randomized for the day of administration of irinotecan (day 1 vs day 3). A total of 36 AS-SCLC patients received 166 courses of treatment at four dose levels. The MTD of irinotecan was 140 mg/m2 (three dose-limiting toxicities, DLTs), and the recommended optimal dose (ROD) 120 mg/m2 (two DLTs). DLTs were febrile neutropenia and grade 3 diarrhea. Other toxicities were mild. No difference in toxicity was seen between the two time schedules. A 77% (95% CI 63.25-90.75%) response rate was recorded among 31 evaluable patients and the median survival was 12 months. The ECI regimen was well tolerated and showed considerable activity in patients with AS-SCLC. Phase II/III evaluation is ongoing. © Springer-Verlag 2005.
Keywords: Cisplatin; Etoposide; Irinotecan; Phase I; Small-cell lung cancer